PENGARUH WINDOW DISPLAY, ARCHITECTURE DISPLAY BAGI MINAT BELI TRANSAKSIONAL PENGUNJUNG BENCOOLEN MALL BENGKULU - Herlin, Herlin; Effendi, Yanto (Creative Research Management Journal, 2023)
The aim of this research was to determine the effect of window displays, architectural displays on the transactional buying interest. Collecting data by distributing questionnaires. with a sample of 150 respondents, measuring using a Likert scale with a purposive sampling method, analyzing data using the IBM SPSS application version 2023. The results prove that Windows display has a positive and significant influence on transactional buying interest. Display architecture has a positive and significant influence on the transactional purchase intention. Simultaneously it proves that together that window display and display architecture have a positive and significant influence on the transactional purchase intention The limitations of this study are the use of questionnaires where sometimes the answers from the respondents do not reflect the actual conditions, time constraints and demographic data of respondents and the variables used are few. This research is expected to be useful for outlets selling at Bencoolen Mall Bengkulu, to increase sales through the arrangement of goods such as window displays, architectural displays